HYGIENIC SIGNIFICANCE OF RISK FACTORS IN DETERMINING THE STRUCTURE OF THE INCIDENCE OF FOOTWEAR WORKERS - Azizova, F.L.; Boltaboev, U.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
to study the structure of the incidence of workers shoe production, as well as risk factors affecting the distribution of diseases in the structure. Material and methods: determined the structure and incidence for 2015-2017. on the basis of appealability to treatment-and-prophylactic institutions of Fergana footwear production workers. The analysis of the health status of workers in selected groups (experimental, control) was carried out, where the primary document was leaflets of temporary disability. Results: the studies conducted in 2015–2017 at the Fergana shoe factory showed a causal relationship between the effects of sustained indicators of severity and tension, factors of the working environment, features of professional affiliation and morbidity among workers depending on gender, age, length of service. The majority of the diseased are women (60%) working in the production workshops, which are the main labor force in the factory. Conclusions: the incidence with temporary disability over the three years both among working women and men increased significantly (P <0.05). In the structure of incidence, the first leading places are occupied by: SARS and influenza (24.0%), diseases of the musculoskeletal system (22.7%), diseases of the connective tissue (19.5%).